Moisture-Wicking Technology in Sports Hijabs - Rivan Saghita Pratama; Erika Afriana; Bintang Reindra Nada Guitara (Physical Activity Journal (PAJU), 2025)
This study discusses the application of moisture-wicking technology to sports hijab as a solution to the challenges of comfort and performance for Muslim athletes. One of the important technologies in the development of sports hijab is moisture-wicking technology, which functions to channel moisture from the skin to the surface of the fabric, thus maintaining user comfort during physical activity. The purpose of this study is to analyze innovations in sports hijab materials and designs that can increase comfort, absorb sweat, and support athlete performance during physical activity. The method used is a literature study and analysis of sports hijab products from various leading brands, by examining material specifications, designs, and their impact on comfort and performance. The results of the study show that the use of materials with moisture-wicking technology, such as a mixture of cotton, rayon, and polyester with special knitting or weaving techniques, can increase air circulation and moisture absorption, so that the hijab remains light and comfortable to wear in various conditions. In conclusion, the development of sports hijabs based on moisture-wicking technology is very important to support the participation and optimal performance of Muslim athletes in various sports